THE INSERTION OF PROLONGED GRIEF DISORDER IN THE DSM-5-TR: Integrative literature review (2020-2024) - Grigoleto Netto, Jose Valdeci (2024)
This study aims to explore the literature on Prolonged Grief Disorder (PGD) following its recent inclusion in the DSM-5-TR, analyzing the implications of this new categorization for interventions with bereaved individuals. To achieve this, the methodology used was an Integrative Literature Review in the databases: PubMed, BVS, and SciELO, using the descriptors: prolonged grief disorder, prolonged grief disorder, and prolonged grief and DSM-5-TR, with works published in the period from 2020 to 2024. A total of 980 articles were found, and after the entire analysis and selection process, 7 studies were included in the research. The results indicate that although the inclusion of PGD in the DSM-5-TR has sparked debates about the medicalization of grief and the potential risks of stigmatization and an expressive number of diagnosis, there is also growing recognition that PGD represents a distinct clinical condition that requires specific intervention. From this, it is concluded that despite the controversy, the recognition of PGD has proven to be a significant advancement in clinical practice, provided it is accompanied by adequate understanding and precise diagnostic criteria, as well as future research being developed to clarify the best therapeutic approaches.